2019
DOI: 10.1287/mnsc.2017.2843
|View full text |Cite
|
Sign up to set email alerts
|

Ex-Day Returns of Stock Distributions: An Anchoring Explanation

Abstract: We offer a new anchoring explanation for the ex-day abnormal returns of stock distributions including stock dividend distributions, splits, and reverse splits. We propose that investors tend to anchor on cum-day prices in valuating ex-distribution stocks, resulting in a positive association between ex-day returns and adjustment factors. We find that this positive return-factor relation exists for all three types of stock distributions and in both the pre-and post-decimalization periods. Furthermore, we find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Studies by Isiker and Tas (2021), Wang et al (2021), Feito-Ruiz et al (2020, Marangu et al (2019), Heavilin and Songur (2019), Chang et al (2019), Lee (2019), Arulsulochana (2019), Khanal and Mishra (2017), Dedman et al (2017), De Ridder andBurnie (2016) and many others have also concluded a positive impact of BSA.…”
Section: Discussionmentioning
confidence: 92%
“…Studies by Isiker and Tas (2021), Wang et al (2021), Feito-Ruiz et al (2020, Marangu et al (2019), Heavilin and Songur (2019), Chang et al (2019), Lee (2019), Arulsulochana (2019), Khanal and Mishra (2017), Dedman et al (2017), De Ridder andBurnie (2016) and many others have also concluded a positive impact of BSA.…”
Section: Discussionmentioning
confidence: 92%
“…This is an important aspect, because when investors are aware that this heuristic might arise, they could consider analyzing the situation better to make more adequate financial forecasts. Other studies have reached similar conclusions, analyzing how the anchoring and adjustment heuristic affects various activities that occur in the field of finance, such as the current value of the P/E ratio and the future forecast of the dividend yield (Fisher & Statman, 2000); the 52-week high price as an explanation for the profits from momentum investing (George & Hwang, 2004); the closing price and 1-day price forecast (Duclos, 2014); the positive relation with the current value of the 52-week high and post-earnings announcement drift (Shin & Park, 2018); and the closing price and the valuation of ex-dividend shares (Chang, Lin, Luo & Ren, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al explain the anchoring effect on the stock market. They point out that when estimating an ex-day stock price, many stockholders will use the cum-day stock price as an anchor point, so that the estimated value will be wrongly biased towards the cum-day stock price [8]. Dobbelstein and Renzing explore the role of the anchoring effect when purchasing health insurance.…”
Section: Literature Reviewmentioning
confidence: 99%